Chimerism in piglets developed from aggregated cloned embryos. Issue 4 (15th March 2016) - Huang, Yongye; Li, Zhanjun; Wang, Anfeng; Han, Xiaolei; Song, Yuning; Yuan, Lin; Li, Tianye; Wang, Bing; Lai, Liangxue; Ouyang, Hongsheng; Pang, Daxin
Abstract : Porcine chimeras are valuable in the study of pluripotency, embryogenesis and development. It would be meaningful to generate chimeric piglets from somatic cell nuclear transfer embryos. In this study, two cell lines expressing the fluorescent markers enhanced green fluorescent protein (EGFP) and tdTomato were used as donor cells to produce reconstructed embryos. Chimeric embryos were generated by aggregating two EGFP‐cell derived embryos with two tdTomato‐cell derived embryos at the 4‐cell stage, and embryo transfer was performed when the aggregated embryos developed into blastocysts. Live porcine chimeras were successfully born and chimerism was observed by their skin color, gene integration, microsatellite loci composition and fluorescent protein expression. The chimeric piglets were largely composed of EGFP‐expressing cells, and this phenomenon was possibly due to the hyper‐methylation of the promoter of the tdTomato gene. In addition, the expression levels of tumorigenicity‐related genes were altered after tdTomato transfection in bladder cancer cells. The results show that chimeric pigs can be produced by aggregating cloned embryos and that the developmental capability of the cloned embryo in the subsequent chimeric development could be affected by the growth characteristics of its donor cell. Abstract : Porcine chimeras are valuable in the study of pluripotency, embryogenesis and development. Two cell lines expressing the fluorescent markers enhanced green fluorescent protein (EGFP) and tdTomato were used as donor cells to produce reconstructed embryos, aggregating embryos at the 4‐cell stage. The live chimeric piglets were largely composed of EGFP‐expressing cells, possibly due to the hyper‐methylation of the promoter of the tdTomato gene.